Notice that the coefficients of the expression 12x+18y-60 are all divisible by 3, then, we have:
![12x+18y-60=3\cdot(4x+6y-20)](https://img.qammunity.org/2023/formulas/mathematics/college/whkflxdf63yqnbwdv1d69fb0lvnv3m3qe0.png)
now notice that the coefficients on the expression inside the parenthesis are divisible by 2, then, we have:
![\begin{gathered} 3\cdot(4x+6y-20)=3\cdot(2\cdot(2x+3y-10))=3\cdot2(2x+3y-10)= \\ =6(2x+3y-10) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/yceh4wpjh020j10jjv79g1x7cqfunmxllk.png)
therefore, the expression as a product of two factors is 6(2x+3y-10)